m-healthcare initiatives for improving outpatient adherence: opportunities and barriers - Cocosila, Mihail; Archer, Norman P.; McMaster eBusiness Research Centre (MeRC) (My University, 2005)
This work is an investigation of the human and system opportunities and barriers, followed by a cost/benefit analysis for outpatient mobile healthcare solutions that could improve adherence to medication and a healthy lifestyle. The goal is to compare the motivators and demotivators for using the technology on one hand, and to identify the main financial aspects on the other hand. The work begins by defining the outpatient adherence problem and how mobile solutions could help. It then discusses the driving and resistance forces among the main stakeholders: patients, healthcare professionals, healthcare institutions, and government. Next it compares the adherence costs and the costs to implement mobile initiatives to combat non-adherence. The possible adoption of mobile healthcare initiatives to address out patient non-adherence, although beneficial, also creates concerns of varying degree for all the major stake holders. These must be addressed before implementation in order to maximize the chances of success.
31 p. : ; Includes bibliographical references (p. 26-28). ; "June 2005".
Keywords: Outpatient; Adherence; Information technology; Mobile healthcare; Business case; Business; E-Commerce; Business; Patient compliance; Medical care; Ambulatory medical care; Medical care > Information technology